Differences in gravity fall between elderly young and the oldest old - Oliveira, Gabriela Guimarães (2017)
Objective: To observe the possible differences in the severity of the decline among elderly young and the oldest old.Methods: We identified all elderly young (60-79 years) and oldest old (80 or older) admitted to fall in 2010, in two Urgent Care Units and Emergency Hospital in Porto Alegre. Upon review of the service bulletins, data were extracted for the elderly, among them, the fall of the consequences, classified by the index proposed by Caberlon and Bos (2015). The mean decrease in severity were compared between the two age groups and tested by Student's t test. The relationship between gender, age and the degree of severity has been tested by chi-square. Results: Most attended were female (72%), among which 24% were long-lived. The percentage of long lifetime was significantly higher than the oldest (19%, p<0.001). The overall average severity score was 5.7. Oldest old showed an index of 6.5±5.45 while the elderly young had a lower rate of 5.5±6.39 (p<0.001). Women showed a higher frequency of severe gravity. Conclusion: We conclude that the oldest old have higher severity of falls. This conclusion also applies to the female sex, and fall more often have higher severity of falls mainly in the number of fractures in the evaluated age groups (young and the oldest old). Also completed is possible to use an assessment tool of decrease in quality that can be used in future research in order to contribute to the achievement of a surveillance more effective and resolute.